Numerical investigation of restricted contact cutting tool in machining of AISI 1045 steel. (2015) - Ma, Jianfeng; Ge, Xianchen; Duong, Nick H.; Lei, Shuting
In this paper, the performance of restricted contact cutting tool in dry orthogonal machining of mild steel (AISI 1045 steel) is investigated using finite element simulations. The rake face length of cemented carbide (WC/Co) cutting inserts is shortened. The aim of this research is to examine the effect of shortened tools on machining performance in terms of the main force, thrust force, and chiptool contact length and to compare them with regular cutting tools. The following restricted tool parameters are examined: length of rake face, alpha angle (the angle between the rake face and the supporting face), and edge radius. It is concluded that restricted contact cutting tools generate lower cutting force and thrust force and consequently lower the energy necessary for machining. The length of rake face, the angle between the rake face and the supporting face, and edge radius all have influence on cutting force in their own ways. This research provides insightful guidance for designing restricted contact cutting tools. [Received 21 May 2014; Revised 25 January 2015; Accepted 26 January 2015]